Synthesis and biological evaluation of the [d-MeAla11]-epimer of coibamide A. Issue 2 (15th January 2015) - Nabika, Ryota; Suyama, Takashi L.; Hau, Andrew M.; Misu, Ryosuke; Ohno, Hiroaki; Ishmael, Jane E.; McPhail, Kerry L.; Oishi, Shinya; Fujii, Nobutaka
Graphical abstract